Regulating online medical records in Malaysia: confidentiality of information / Mohd Shazmeer Zamhari ...[et al.] - Zamhari, Mohd Shazmeer; Baharuddin, Nur Elissa; Samad, Nurul Atikah; Mohd Noh, Siti Nurfadzilah (2011)
Medical confidentiality is a familiar issue in the medical world. The general common law duty is, it is imposed on a doctor to respect the patient's confidence bestowed upon them, as was seen in the case of Stephens v. Avery} Disclosure of confidential information is part of the legal process. This is seen as there are case laws showing that the law protects the medical confidentiality of patients, and that the doctors are obliged to not disclose the information they have on their patients. One of the established cases is the case of Hunter v Mann.2 This was at the time where medical information was on paper.3 Basically, the confidential information is in written form, documented in other words. However, nowadays, due to globalization and the advancement in technology, medical information has seen to progress in terms of its accessibility thus provide efficiency in work done as less time needed to access the database. Today, there is online medical database. The term 'medical' relates to the study and practice of medicine, which concerns about maintaining and restoring health by the prevention and the treatment of illnesses whereas 'online database' is a database accessible from a network, including the internet.4 Hence, online medical database is where medical records are accessible online via the internet. Due to this, there are several issues or concerns which arise. Online medical record is open to abuse by an unauthorized and irresponsible person such as hackers and this is one of many issues which may arise.5 Moreover, the argument on making medical information more accessible seems to defeat the purpose for the people in rural areas because of their lack of exposure to internet accessibility.6 Another issue that could be at hand is when this particular service is prone to be abused by politicians to play their propaganda game as they may use the personal information which is obtained unlawfully to deteriorate the status of a politician from opposition party.